2022
DOI: 10.1155/2022/7001392
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation on Deep Learning Model of College English Based on Multimodal Learning Method

Abstract: Deep learning refers to active learning that allows students to perceive, experience, understand, and apply knowledge. Deep learning focuses on the mastery of knowledge and skills and more on the cultivation of higher-order thinking skills such as awareness, problem-solving, and knowledge transfer. In order to improve the quality of English classroom teaching in today’s colleges and universities and cultivate high-level applied foreign language talents, this paper constructs a multimodal teaching model based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Deep learning principles have the potential to significantly enhance language acquisition in higher education by leveraging advanced technologies and innovative teaching methodologies (Han, 2022;Matsushita et al, 2018;OpenAI, 2023). This aligns with the idea that education should focus on meaningful learning experiences (Vargas-Hernández & Vargas-González, 2022).…”
Section: Deep Learning and Meaningful Pedagogy In Language Acquisitionmentioning
confidence: 75%
See 1 more Smart Citation
“…Deep learning principles have the potential to significantly enhance language acquisition in higher education by leveraging advanced technologies and innovative teaching methodologies (Han, 2022;Matsushita et al, 2018;OpenAI, 2023). This aligns with the idea that education should focus on meaningful learning experiences (Vargas-Hernández & Vargas-González, 2022).…”
Section: Deep Learning and Meaningful Pedagogy In Language Acquisitionmentioning
confidence: 75%
“…Bridging these gaps is crucial, as it addresses the imperative of providing students with holistic language education in an AI-driven world. The work of Han (2022) sheds light on deep learning models in college English based on multimodal learning methods, while McPhail (2021) emphasizes the search for deep learning and the importance of curriculum coherence. Winje and Løndal (2020) provide a systematic mapping review of decades of research in primary and secondary education, focusing on deep learning, and their findings contribute to the context of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Academics worldwide have discussed using LOTS and HOTS to improve language learning, course design and assessment (Alfarisy et al , 2023; Astrid et al , 2022; Balfaqeeh and Hassan, 2017; Erdiana and Panjaitan, 2023; Han, 2022; Hubers, 2022; Jin, 2020; Johansson, 2020; Kholifiatin et al , 2019; Kosasih et al , 2022; Muhayimana et al , 2022; Nair et al , 2019; Obenchain and Ives, 2006; Othman et al , 2016; Prakash and Litoriya, 2022; Shalaby and Mitry, 2017; Tsaparlis, 2020; Valentová et al , 2021; Yamat et al , 2019). Over and above the facts that HOTS help learners develop critical thinking, logical and analytical skills, it is to be understood that these thinking functions work independently rather than based on previous knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%